STUDI PETROLOGI DAN MINERALOGI LAVA GUNUNG TANJAKNANGSI, KABUPATEN BANDUNG, JAWA BARAT - Naufal Prasetya, Abrar
Previous studies in Mount Tanjaknangsi area have discussed regional geological settings but more specific studies using more advanced mineralogical analysis have not been conducted by previous researchers. The purposes of this study are to explain the geological settings, characteristics of magma, and magma evolution in the Mount Tanjaknangsi area and its surroundings. Petrological and mineralogical analysis were carried out on nineteen volcanic rock samples of Mount Tanjaknangsi. Mineral chemistry data analyzed from 7 (seven) representative samples from Mount Tanjaknangsi using SEM-EDS JEOL JSM-IT-300. Based on the observation, Research area can be divided into 3 (three) geomorphological units consist of Tanjaknangsi Lava Flow Ridge Unit, Tarikolot Pyroclastic Flow Unit and Cijalupang Alluvial Plain Unit. The 4 (four) lithologies of the study area are Tanjaknangsi Pyroxene Andesite Lava Unit 1 (Tl1), Tanjaknangsi Pyroclastic Breccia Unit (Ta), Tanjaknangsi Pyroxene Andesite Lava Unit 2 (Tl2), and Alluvial Deposition Unit. Petrologycal analysis shows that those rocks are pyroxene andesite consisting of plagioclase, pyroxene, olivine, and opaque minerals phenocrysts. While opaque minerals, plagioclase microlites, pyroxene and volcanic glass are the composition of the groundmass. The evolution of magma on Mount Tanjaknangsi began with magma which had a temperature of 890?–1020°C and formed the Tanjaknangsi Pyroxene Andesite Lava Unit 1 (Tl1). These magma were intense on convection and adiabatic compression process which had produced Tanjaknangsi Pyroclastic Breccia Unit (Ta) with 940?–980°C after that. Magma injection occurred and the magma temperature changed to 910?–1090?C which resulted the formation of Tanjaknangsi Pyroxene Andesite 2 Lava Unit (Tl2). The magma affinity of the these units are calc-alkali.